BAHASA PROKEM DAN PEMBELAJARAN BAHASA INDONESIA - Juanda Juanda (RETORIKA: Jurnal Bahasa, Sastra, dan Pengajarannya, 2012)
Abstract: Slang language and the learning of  Indonesian. This study aimed to describe slang language and its influence on the Indonesian language. The data was collected through interviews, records, stimulating-writing,, and introspection. The source of the data was the conversation of the teenagers especially those who lived in Rawamangun eastern part of Jakarta. The results showed that the slang language produced by teenagers, were in the form of vocabularies of : acronyms, abbreviations, replacements of phonemes at the beginning of the second or third syllable, English terms, terms of reference, and flipping spoken word. The structure of the slang language were in the form of words that have formed in a simple, short, methatesis, and English term, words that have been formed in complex formation, and also words that have been formed in unclear way. While the  pattern of meaning of slang language is based on : figure of speech, irony, euphemisms, and methapores. Abstrak: Bahasa Prokem dan Pembelajaran Bahasa Indonesia. Penelitian ini bertujuan men-deskripsikan bahasa prokem dan pengaruhnya terhadap bahasa Indonesia. Pengumpulan data dilakukan melalui wawancara, rekam, pancing, catat, dan instrospeksi. Hasil penelitian menun-jukkan percakapan remaja yang berdomisili di Kota Jakarta, khususnya remaja yang ada di Jakarta Timur, Rawamangun kosakata bahasa prokem berupa: akronim, singkatan, penggantian fonem pada awal suku kata kedua/ketiga, bahasa Inggris, istilah acuan, dan membalik kata. Struktur ba-hasa prokem  berupa kata yang menga-lami bentukan secara sederhana, singkatan, metatesis, isti-lah bahasa Inggris, kata yang mengalami bentukan kom-pleks, dan kata yang tidak jelas proses pembentukannya. Pola makna bahasa prokem berdasarkan majas: ironi, eufe-misme, dan metafora. Kata kunci: bahasa prokem, struktur, dan makna